2017
DOI: 10.1590/1980-5373-mr-2017-0481
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Evolution and Modeling of Growth Kinetics of L12-structured Al3Zr Particles in Al-0.22Zr and Al-0.32Zr (wt.%) Alloys Isothermally Aged

Abstract: The microstructure and microhardness of isothermally aged Al-0.22Zr and Al-0.32Zr alloys were investigated. Peak microhardness occurred after aging at 650K for 100 h for both alloys and decreased slightly after aging at 400 h. Nanometer-scale spherical L1 2 -structured Al 3 Zr precipitates were observed using Transmission Electron Microscopy, these presented r < 7 nm at the center of dendrite branches. In the Al-0.32Zr alloy, particles increased in radius after aging at 650 K from 100 to 400 h while in the Al-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
2
0
5
Order By: Relevance
“…Indeed, back to eq. (ii) Souza et al [45] showed that high cooling rate can suppress Al3Zr phase precipitation. Shigenori Hori et al [46] even draw the 32 transition between precipitation of Al3Zr structure and αAl supersatured state according to cooling rate and Zr content for Al-Zr alloys (Figure 21).…”
Section: Resumption Of Columnar Growthmentioning
confidence: 99%
“…Indeed, back to eq. (ii) Souza et al [45] showed that high cooling rate can suppress Al3Zr phase precipitation. Shigenori Hori et al [46] even draw the 32 transition between precipitation of Al3Zr structure and αAl supersatured state according to cooling rate and Zr content for Al-Zr alloys (Figure 21).…”
Section: Resumption Of Columnar Growthmentioning
confidence: 99%
“…Esse resfriamento rápido foi realizado A liga de maior concentração em zircônio (0,32%p.Zr) e maior grau de deformação (70%) apresentou uma maior quantidade de precipitados Al 3 Zr, o que indica a contribuição do aumento de concentração de zircônio e da deformação para aumentar a quantidade dessas partículas. A força motriz para precipitação é maior nas ligas com maior concentração em zircônio, de modo que favorece o aumento no número de precipitados [4][5][6][7][8]. As discordâncias geradas após deformação são sítios que facilitam a precipitação heterogênea pela microestrutura e também favorecem o aumento na quantidade de precipitados.…”
Section: Metodologiaunclassified
“…A redução da microdureza entre 100 e 400 horas é devido ao superenvelhecimento da liga que ocorre devido o coalescimento dos precipitados [6][7][8][9]. Esse comportamento também foi observado por Souza [6].…”
Section: Microdurezaunclassified
See 1 more Smart Citation
“…One disadvantage of the interdendritic channels is that they are usually weaker and more susceptible to failure relative to other regions because of the fewer and bigger precipitates present. This leads to deleterious effects on the mechanical properties [30,31,82].…”
Section: Thermal Aging and Tensile Testmentioning
confidence: 99%